Structure-function studies can improve binding affinity of cohesin-dockerin interactions for multi-protein assemblies - Duarte, Marlene (2022)
the Associate Laboratory for Animal and Veterinary Sciences (AL4AnimalS) grant LA/P/0059/2020. LA/P/0140/2020 of the Associate Laboratory Institute for Health and Bioeconomy - i4HB. National Institutes of Health R01-GM129325 and the Office of Cyber Infrastructure and Computational Biology, National Institute of Allergy and Infectious Diseases. Publisher Copyright: © 2022 The Author(s)